Հայ հասարակության պատմական հիշողության հավաքական պատկերը - Պողոսյան, Գևորգ; Պողոսյան, Ռիմա (Լիմուշ հրատ.)
The article provides an analysis of the results of the nationwide representative sociological survey devoted to the study of the features of the historical memory of modern Armenian society. Based on the empirical data obtained, the historical depth, structure and national characteristics of the collective social memory of the population are analyzed.
Keywords: Սոցիոլոգիա